1997
DOI: 10.1115/1.2817030
|View full text |Cite
|
Sign up to set email alerts
|

The Advanced Cooling Technology for the 1500°C Class Gas Turbines: Steam-Cooled Vanes and Air-Cooled Blades

Abstract: It is very essential to raise the thermal efficiency of combined cycle plants from the viewpoint of energy saving and environmental protection. Tohoku Electric Power Co., Inc., and Toshiba Corporation in Japan have jointly studied the next generation of combined cycle systems using 1500°C class gas turbine. A promising cooling technology for the vanes using steam was developed. The blades are cooled by air, adopting the impingement cooling, film cooling, and so on. The cooling effectiveness was confirmed both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Advanced technology gas/steam combined cycle configuration having a simple gas turbine in topping cycle and reheat steam turbine in bottoming cycle as shown in figure 1 has been con-Sid. ered [4,6]. Turbine stages are internally cooled employing water/steam as coolant.…”
Section: Configurationmentioning
confidence: 99%
“…Advanced technology gas/steam combined cycle configuration having a simple gas turbine in topping cycle and reheat steam turbine in bottoming cycle as shown in figure 1 has been con-Sid. ered [4,6]. Turbine stages are internally cooled employing water/steam as coolant.…”
Section: Configurationmentioning
confidence: 99%
“…However, with the extremely high temperatures of the combustion gases it became apparent that film cooling causes increased production of NOx as well as a decreased in the aerodynamic efficiency of the turbine blade. As a remedy, a highpressure closed-circuit internal cooling concept [3] became attractive again decades after its inception. Moreover, circular cross-section straight-through coolant passages became attractive because of the ease of their manufacturing thus lower cost of such blades.…”
Section: Design Optimization Of Coolant Passages Of a Turbine Bladementioning
confidence: 99%
“…Jordal and Torisson [7] have shown that replacing the air-cooling system of the vanes with steam in a closed loop had around 1.5 percentage points increase in thermal efficiency. Nomoto et al [8] pointed out that under high-pressure steam fluid conditions the inner convection cooling achieves enough cooling efficiency and can replace air-cooling. Bohn and his group [9,10] made systematic experimental and numerical investigation of a steam-cooled vane, which had 22 straight radial cooling passages.…”
Section: Introductionmentioning
confidence: 99%